Ureditev začasnega in občasnega dela študentov s poudarkom na spremembah ZUJF-C - Bobovnik, Andraž (Delavci in delodajalci, 2015)
In the first part of the text the author summarizes legal framework in the area of temporary and occasional work of students, better known as student work, with focus on the last changes in this area. Act Amending the Fiscal Balance Act that came in to force on the 1st of February 2015 is bringing about important changes in the area of student work. That is why in the second part the article focuses on key changes for students, student agencies and employers in this area.
Keywords: delovno pravo; dijaki; honorarno delo; pravice; pravna ureditev; študenti; trg dela